The Influence of Wordwall-Assisted Problem-Based Learning (PBL) on Electrical Energy Concept Mastery Reviewed from the Prior Knowledge of Fifth-Grade Elementary Students - Minarsih; Parji; Marheny Lukitasari (Postgraduate, University of Mataram, 2026)
While Problem-Based Learning (PBL) and Wordwall have been studied individually, empirical research integrating both to address abstract science topics in elementary schools remains limited, leaving a gap in understanding how this combination interacts with students' prior knowledge. This study analyzes the influence of the Wordwall-assisted PBL model on fifth-grade students’ mastery of electrical energy concepts, considering their prior knowledge. A quantitative quasi-experimental design with a posttest-only control group was used, involving a total sample of 33 students (17 in the experimental class and 16 in the control class). Instruments included validated and reliable prior knowledge and concept mastery tests. Two-Way ANOVA results show significant main effects on concept mastery based on the learning model and prior knowledge levels (p < 0.05). The experimental group achieved a notably higher mean score (88.75) compared to the control group (66.50), with the learning model exerting a strong effect size (Partial Eta Squared, = 0.872) on concept mastery. Crucially, no significant interaction effect was found between the learning model and prior knowledge (p = 0.861), indicating that the Wordwall-assisted PBL model consistently and uniformly enhances learning outcomes for students across all initial ability levels